Evaluating the benefits of augmented reality for task localization in maintenance of an armored personnel carrier turret - Henderson, Steven J.; Feiner, Steven (2009 8th IEEE International Symposium on Mixed and Augmented Reality, 2009)
We present the design, implementation, and user testing of a prototype augmented reality application to support military mechanics conducting routine maintenance tasks inside an armored vehicle turret. Our prototype uses a tracked head-worn display to augment a mechanic's natural view with text, labels, arrows, and animated sequences designed to facilitate task comprehension, location, and execution. A within-subject controlled user study examined professional military mechanics using our system to complete 18 common tasks under field conditions. These tasks included installing and removing fasteners and indicator lights, and connecting cables, all within the cramped interior of an armored personnel carrier turret. An augmented reality condition was tested against two baseline conditions: an untracked headworn display with text and graphics and a fixed flat panel display representing an improved version of the laptop-based documentation currently employed in practice. The augmented reality condition allowed mechanics to locate tasks more quickly than when using either baseline, and in some instances, resulted in less overall head movement. A qualitative survey showed mechanics found the augmented reality condition intuitive and satisfying for the tested sequence of tasks.